Association between Peripheral Oxidative Stress and White Matter Damage in Acute Traumatic Brain Injury. (3rd April 2014) - Lin, Wei-Ming; Chen, Meng-Hsiang; Wang, Hung-Chen; Lu, Cheng-Hsien; Chen, Pei-Chin; Chen, Hsiu-Ling; Tsai, Nai-Wen; Su, Yu-Jih; Li, Shau-Hsuan; Kung, Chia-Te; Chiu, Tsui-Min; Weng, Hsu-Huei; et al.
Abstract : The oxidative stress is believed to be one of the mechanisms involved in the neuronal damage after acute traumatic brain injury (TBI). However, the disease severity correlation between oxidative stress biomarker level and deep brain microstructural changes in acute TBI remains unknown. In present study, twenty-four patients with acute TBI and 24 healthy volunteers underwent DTI. The peripheral blood oxidative biomarkers, like serum thiol and thiobarbituric acid-reactive substances (TBARS) concentrations, were also obtained. The DTI metrics of the deep brain regions, as well as the fractional anisotropy (FA) and apparent diffusion coefficient, were measured and correlated with disease severity, serum thiol, and TBARS levels. We found that patients with TBI displayed lower FAs in deep brain regions with abundant WMs and further correlated with increased serum TBARS level. Our study has shown a level of anatomic detail to the relationship between white matter (WM) damage and increased systemic oxidative stress in TBI which suggests common inflammatory processes that covary in both the peripheral and central reactions after TBI.